Difference between U-19 and U-16 football players in Breidablik in 30-meter sprint - Dean Edward Martin 1972- (2016)
The purpose of this study was to measure the speed of the players in the U-19 and U-16 in Breidablik over 30 meters. This research was carried out because speed is a big aspect of the game of football, so by preparing the younger generation with proper training and techniques would give the individuals a better chance of succeeding in senior football when the time comes. There were two groups that took part in this research with ages ranging from 15-19 years old. The younger group were 15-16 years old and the older group were between 16-19. There were twenty players that took part in the research, ten players in each group. The results of the research indicated that there was a significant difference between the groups with the older group running faster. Further research into testing in football should be carried out on this subject in Iceland. By finding out what would be the best methods for speed improvement and putting speed training into practice from an early age. The tests need to be more sports specific and be individualised. Testing after what position a player plays could save time in picking players for positions at a young age. Testing is going to give coaches a platform to work from with regards to speed.